THE RELATION BETWEEN PATIENTS' PERCEPTION OF CONTINUOUS AMBULATORY PERITONEAL DIALYSIS (CAPD) AND SELF-EFFICACY IN PATIENTS WITH CAPD - Yohanes Gamayana; Yulia Yulia; Lestari Sukmarini (JURNAL KEPERAWATAN CIKINI, 2021)
Background: CAPD is one of a few therapy that can be used to replace the kidney function. A good patient perception of CAPD can increase the self-efficacy of patients undergoing CAPD. The majority of CAPD patients are HD patients who have a perceived experience of both physical and psychological discomfort. The research objective was to determine the relation between perceptions of CAPD measures and self-efficacy in patients undergoing CAPD. Methods: This study used a cross-sectional approach. The number of samples of 75 respondents was selected by consecutive sampling technique. Results: The logistic regression test results show that there is a relation between perceptions of CAPD measures and self-efficacy in patients undergoing CAPD with the confounding variable that affected by social support. Conclusions: Nurses need to improve their abilities when assessing patient perceptions and increasing the role of social support, so that the information obtained becomes the basis for increasing self-efficacy in patients undergoing CAPD.